Castrating the Authority in El Sadaawi’s play Isis - Shoaib , Muhammad (Journal of Research in Humanities, 2023)
This paper on the Egyptian feminist playwright Nawal El Sadaawi’s play Isis (1986) seeks to explore the psychological and social dimensions of castration by applying the Slovenian Marxist and Lacanian philosopher Slavoj Žižek’s ideas on symbolic castration, ideological fantasy and mask. The focus will be on Žižek’s understanding of Lacan’s ideas on symbolic castration. It will be proved that Ra, Seth and their state machinery are castrated from within. But in order to conceal their inner castration, they create a symbolic order of power and masculinity. The role of female gaze, stage props, theatrical devices, language and gestures as tools of deconstruction and castration will be discussed to highlight the castration anxiety, and the symbolic castration of Ra and Seth.